Value Co-Creation in 24/7 Services Generated by Generative Artificial Intelligence - Sarosto, Kristian (2025)
This master’s thesis examines the transformative potential of Generative Artifi-cial Intelligence (GEN AI) in advancing value co-creation within the context of 24/7 digital services, with a particular focus on Finnish trade unions and their career and legal services. The study investigates how GEN AI influences ser-vice delivery and value co-creation processes and identifies key considerations for its effective adoption. The theoretical framework is based on service-dominant logic and micro-level mechanisms, which provide an in-depth un-derstanding of value co-creation in services. Using a qualitative research ap-proach, thematic interviews with experts revealed the opportunities and chal-lenges of GEN AI, particularly in improving service accessibility, efficiency, and personalization. The findings highlight the importance of ensuring reliabil-ity, data security, and ethical considerations in sensitive trade union services. This research offers strategic recommendations for trade unions to adapt to technological developments and meet the evolving needs of their members